2020
DOI: 10.3390/brainsci10100724
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Appraisal of the Effect of Amplitude on the Stability of Interlimb Coordination Based on Tightened Normalization Procedures

Abstract: The stability of rhythmic interlimb coordination is governed by the coupling between limb movements. While it is amply documented how coordinative performance depends on movement frequency, theoretical considerations and recent empirical findings suggest that interlimb coupling (and hence coordinative stability) is actually mediated more by movement amplitude. Here, we present the results of a reanalysis of the data of Post, Peper, and Beek (2000), which were collected in an experiment aimed at teasing apart t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Before calculating the relative phase angle, we performed half-cycle normalization to avoid phase angle distortion due to variations in oscillation center and movement frequency 28 , 29 . First, we defined half-cycles by detecting maximum and minimum peaks of girth of chest and waist respectively with the “findpeaks” function in MATLAB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before calculating the relative phase angle, we performed half-cycle normalization to avoid phase angle distortion due to variations in oscillation center and movement frequency 28 , 29 . First, we defined half-cycles by detecting maximum and minimum peaks of girth of chest and waist respectively with the “findpeaks” function in MATLAB.…”
Section: Methodsmentioning
confidence: 99%
“…First, we defined half-cycles by detecting maximum and minimum peaks of girth of chest and waist respectively with the “findpeaks” function in MATLAB. The displacement data was normalized by centering per half-cycle by subtracting the center value between minimum and maximum peaks of the respective half-cycle bin 28 . The velocity was normalized by dividing each half-cycle of the velocity by , where is the corresponding half period 29 .…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, research has shown that constraint alterations can evoke beneficial changes in a motor system by training it to adapt to changes in the environment (Davids et al, 2003(Davids et al, , 2008Sch€ ollhorn et al, 2006Sch€ ollhorn et al, , 2009Sch€ ollhorn et al, , 2010Sch€ ollhorn et al, , 2012. On the other hand, research on resilience losses in biological and motor systems points out that the exposure to repeated (minor) stressors can undermine resilience leading to negative changes in the system's level of functioning (Bootsma et al, 2002;Cuijpers et al, 2019;Dai et al, 2012;De Poel et al, 2020;Richardson et al, 2007;Scheffer et al, 2009Scheffer et al, , 2012Van de Leemput et al, 2014). These lines of research indicate opposite predictions for the effect of repeated constraint alterations on a motor system.…”
Section: Discussionmentioning
confidence: 99%
“…This means that during critical slowing, encountering a relatively minor stressor that would normally be overcome may already be sufficient to cause a transition to an undesired state (Kelso, 1984;Sch€ oner & Kelso, 1988;Van de Leemput et al, 2014). Accordingly, research on coordination dynamics has shown that alterations to the amplitude of a movement (De Poel et al, 2020) and restricting visual information (Bootsma et al, 2002;Cuijpers et al, 2019;Richardson et al, 2007) during a rhythmic motion task can severely disrupt the coordinated motor performance. For example, Bootsma and colleagues (2002) showed that repeated restriction of visual information forced individuals to adapt their movement patterns and reduce their movement time, similar to effects of increased task difficulty.…”
Section: The Resilience Processmentioning
confidence: 99%
“…We set this band while considering the predicted frequency of the basic rhythmic movements described in the introduction. Additionally, applying the high-pass filter is one of the preferred methods by which to exclude data trends and calculate the appropriate phase (de Poel et al, 2020). After smoothing and adjusting the data for phase analysis, we applied a typical normalizing procedure to subtract the whole mean and divide by the standard deviation.…”
Section: Methodsmentioning
confidence: 99%